(untitled) (Experimental biology, 2019)
In human diseases and physiology, the function of miRNAs is expanding; however, especially nucleotide repeats disorder the majority of miRNA - driven regulatory structure is remaining uncertain. The aim of this work is to reveal which candidate genes of nucleotide repeat diseases and in which degrees can interact with miRNA. We present results on the interaction of 2567 miRNAs with mRNA 102 candidate genes of having nucleotide repeats using the MirTarget program. miRNAs binding sites in the CDS mRNAs of 36 genes from 102 candidate genes with nucleotide repeats have been shown. Among miRNAs that bind with high energy to mRNA genes with nucleotide repeats, we choose five miRNAs that have binding sites for two or more genes: miR-3656 (ARX, EP400, HTT, NCOR2); miR-3960 (ARX, CACNA1I, HTT); miR-1322 (ATN, EP400, GIGYF2, HTT, NCOR2); miR-1281 (CACNA1I, HRC, HTT); miR-4279 (CACNA1I, NCOR2). It was determined that considering miRNAs binding sites are located mainly in regions with CAG, GCG, GAG repeats. Neurological disorders are known to be caused by an increased number of CAG, GCG, GAG repeats, typically in coding regions of otherwise unrelated proteins. Better understanding of interaction specificity of miRNAs and genes promises to offer further in sights into the pathogenic pathways of trinucleotide repeats expansion disorders. Keywords: miRNA, mRNA, coding sequence, binding site, trinucleotide repeat.